A massless pulley of diameter 50mm has a massless cord around it connected to two hanging containers of sugar. For the part I'm working on, one container has mass 520g, and the other has mass 480g. They start out at rest at the same level. I need to find the acceleration of the center of mass when they are released. This is what I've done:

The center of mass has zero acceleration in the horizontal direction. For the vertical direction, I use F(net)=Ma(com), or a(com)=F(net)/M. M is just the total mass, or .52kg+.48kg= 1.00kg. Then I have F(net)= F1-F2=m1g - m2g=(m1-m2)g= (.52kg-.48kg)(9.8m/s^2) = .04kg*9.8m/s^2= .392N. So a(com)=.392N/1.00kg = .392m/s^2. However, the answer in the back of the book is -1.6x10^-2 m/s^2. What am I doing wrong (besides the sign convention)??? I thought maybe I needed the tension in the string for F(net), but I thought they would cancel. If it is the tension, how does that fit in? I never liked pulley problems...